Survey, Question, Read, Resite, Review (SQ3R) to Improve Reading Comprehension Skills - Lusi Maryuni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning Indonesian is a compulsory subject that needs to be taught to students in elementary schools (SD). Because Indonesian has an important role to improve the ability of students to communicate in writing and orally. Reading activities can take a person further and deeper than other language skills. Reading activities require understanding so that the message carried by the text can be absorbed optimally. Reading comprehension ability can be improved through the application of the SQ3R method. The purpose of this study is to describe the concept of SQ3R, reading comprehension, and the application of SQ3R in improving reading comprehension skills. The result of this study is that the application of SQ3R in reading activities can improve students' reading comprehension skills.